Mouse NG2(+) Oligodendrocyte Precursors Express mRNA for Proteolipid Protein But Not Its DM-20 Variant: A Study of Laser Microdissection-Captured NG2(+) Cells - Ye, Ping (J Neurosci, 2003)
Despite recent advances in our understanding of lineage of oligodendrocytes, detailed molecular characterization of this lineage in vivo is limited, primarily because of our inability to obtain a pure population of cells in situ. To define the molecular characteristics of oligodendrocyte lineage cells during development and their response to injury, we developed a strategy that uses laser capture microdissection (LCM) to isolate cells from sections and reverse transcription-PCR to determine mRNA expression. As a first step, we examined the expression of myelin-specific protein genes in NG2(+) cells in cerebral cortex. We demonstrate that NG2(+) cells in both developing and adult mice express NG2 mRNA but not mRNA for proteins specific for astrocytes, neurons, or microglia, indicating that a highly pure population of antigen-specific cells of the oligodendrocyte lineage can be obtained using LCM. Furthermore, we show that NG2(+) cells express mRNAs for proteolipid protein (PLP), myelin basic protein, and 2′,3′-cyclic nucleotide 3′-phosphodiesterase, but they dot not express DM-20 mRNA, a PLP mRNA splicing variant. Our data demonstrate that antigen-specific cells of oligodendrocyte lineage differentially express mRNA for myelin-specific proteins and their variants in vivo, partly define the gene expression in NG2(+) cells, and raise questions about the cellular sites of DM-20 expression. This work also shows that LCM is a valuable tool to define and analyze gene expression in the cells of the oligodendrocyte lineage.